2021
DOI: 10.1108/imefm-06-2020-0301
|View full text |Cite
|
Sign up to set email alerts
|

Do sukuk spur infrastructure development?

Abstract: Purpose This paper aims to examine the effect do Sukuk Spur Infrastructure Development of Sukuk market expansion on infrastructure development for a sample of 15 emerging countries over the period 1997–2018. The paper also compares the role of Sukuk in infrastructure development to that of the size of the banking system, bond market development and stock market development. Design/methodology/approach A novel index of infrastructure development is constructed via principal component analysis. This index is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…The explanation above is in line with research conducted by Smaoui, Mimouni and Ben Salah (2021) stated that Sukuk has great potential as capital for the development of state infrastructure. Transparency in the Sukuk financing model minimizes corruption by the government.…”
Section: Alternative Budget Other Than Debt For the Statesupporting
confidence: 81%
“…The explanation above is in line with research conducted by Smaoui, Mimouni and Ben Salah (2021) stated that Sukuk has great potential as capital for the development of state infrastructure. Transparency in the Sukuk financing model minimizes corruption by the government.…”
Section: Alternative Budget Other Than Debt For the Statesupporting
confidence: 81%
“…However, different results were obtained by Grassa & Gazdar (2014) and Echchabi et al (2018), who found that the development of sukuk in GCC countries did not have an impact on economic growth as proxied by GDP, Gross Capital Formation (GCF) and trading activities. Meanwhile, Smaoui, Mimouni, & Ben Salah (2021) note that sukuk has a positive relationship with infrastructure development. Based on these studies, we propose the following hypotheses: H1: Islamic banking financing has a positive and significant impact on the real sector in the short and long term.…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%
“…Sukuk is one of the Islamic Finance instruments that plays a role in supporting the country's economic growth through government projects, so that economic growth has increased. During the period of sukuk issuance until the project is completed and a well-developed sukuk market will contribute to the expansion of the country's infrastructure (Al Fathan & Arundina, 2019;Smaoui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%